Dari Kampus untuk Umat: Berbagi Takjil sebagai Wujud Pengabdian Mahasiswa di Bulan Ramadan - Pandu Rudy Widyatama; Putresa Eka Irmandini; Rheyna Putri Arditiya; Titis Nurussama Nilakandi; Nurul Ainni (Jurnal Pengabdian Cendekia, 2025)
Takjil sharing activities during the month of Ramadan are a form of social concern that involves students in community service. This research aims to develop a structured takjil sharing program and evaluate its social impact on the beneficiary community. The method used is Participatory Action Research (PAR), which actively involves students in each stage of the activity. The results of the study showed that this activity ran smoothly despite several obstacles such as delays in distribution and student fatigue. The implemented solutions, such as a more equitable distribution of tasks and a more efficient distribution system, successfully solved the problem. This program not only provides social benefits to the community but also enriches the student experience in social service. Going forward, the importance of careful planning and the involvement of more parties will increase the sustainability and impact of these activities.